Retracted: Wuju Opera Cultural Creative Products and Research on Visual Image Under VR Technology - Yahong Wang; Xiaobing Hu (IEEE Access)
Wuju Opera is a form of Chinese traditional culture, and there are many visual elements that provide designers with a source of creativity. This research mainly discusses the development of cultural and creative products of Wuju Opera and the visual image under VR technology. First of all, three-dimensional modeling technology is the basis for establishing virtual scenes, modeling objects on the stage, including stages, props, and the synthesized video lens movement effect is consistent with the lens parameters of the physical camera to avoid causing the target foreground to “float” the situation on a virtual background. Interaction capabilities are given to some objects, such as the opening of curtains and lights, which can be completed through user interaction. Secondly, introduce the related knowledge of Wuju Opera through some text, pictures and other materials, in order to achieve a deeper understanding of Wuju Opera and the purpose of like Wuju Opera. Finally, by connecting the VRML virtual scene with the database, users can quickly call the corresponding virtual Wuju Opera performance fragments. The VR-Platform platform is used to establish a virtual three-dimensional landscape planning scene, and the roaming function can be realized by making cameras and adding collision detection. By connecting to the database, information can be searched, and the audience can be immersed when roaming by adding music and special effects. The similarity of the characters presented under VR technology is 93%, and the audience’s satisfaction with the drama under VR technology is 95%. The research results show that the visual simulation effect developed based on VR technology has the necessary texture, color, shadow and other changes. It feels the same as the drama on the plane. It is vivid and makes people feel the real feeling, which is beneficial to Wuju Opera.